Spatial Dynamics of Land Use Changes and Land Carrying Capacity of Settlement in Palaran District Year 2014 – 2024 - Randi Arman Pratama; Ananto Aji; Juhadi Juhadi (JPG (Jurnal Pendidikan Geografi), 2025)
This study examines spatial dynamics of land use change and the capacity of land to support residential development in Palaran Subdistrict, Samarinda City, over a ten-year period. The objectives are to map temporal shifts in land cover for 2014, 2019, and 2024; to evaluate land suitability for housing based on eight bio-physical parameters stipulated by national regulation; and to quantify the carrying capacity and population support capacity of suitable land. The methodology integrates multitemporal satellite imagery processing, supervised classification with a random decision forest  algorithm, geographic information system overlay analysis, and field validation at two hundred sampling points. Results reveal a forty-one percent increase in built-up area and a seventy-percent decrease in agricultural land, with over eighty-seven percent of the study area classified as highly suitable for residential use. Calculations of land support capacity indicate a significant surplus relative to current population levels, underscoring opportunities for sustainable urban expansion and evidence-based spatial planning.